Intake of Maillard reaction products reduces iron bioavailability in male adolescents - García, Marta Mesías; Seiquer, Isabel; Delgado-Andrade, Cristina; Galdó, Gabriel; Navarro, Maria Pilar (Molecular nutrition & food research, 2009)
The effects of diets with different Maillard reaction products (MRPs) content on biological iron utilization were compared using in vitro/in vivo assays. Diets were rich (brown diet, BD) or poor (white diet) in MRP. In vitro studies included iron solubility after in vitro digestion of diets and iron transport across Caco-2 cells. In the human assay 18 healthy adolescent males (11-14 years) participated in a 2-wk randomized two-period crossover trial. Subjects collected urine and faeces on the last 3 days of each dietary period, and fasting blood samples were obtained after periods. In vitro dietary iron availability was significantly lower with the BD than the white diet (9.52 and 12.92%, respectively), as a consequence of the lower iron solubility after the in vitro digestion, but not as a result of decreased transport of the remaining soluble iron. The BD consumption increased iron fecal excretion (~1.4-fold) and significantly decreased its bioavailability (~2.7-fold), mainly due to the effects found at digestive level. Serum biochemical parameters related to iron metabolism remained unaltered. It is concluded the presence of MRP in the diet negatively affects iron bioavailability. As iron deficiency may be related to learning impairment and to reductions of cognitive and physical functions, possible long-term effects of excessive MRP intake during adolescence warrant attention.